The Effect Of Leading Types On The Job Satisfaction In The Higher Education Sector – Comparison Study Between The Higher Institute Of Business Administration & The Higher Institute Of Administrative Development, - زكريا سلامة (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The research aims at identifying the leading types in the Higher Institute of Business Administration & The Higher Institute of Administrative Development and to identify the effect of such types on job satisfaction and the relationship between them . The research covered 167. The research consists of five main chapters, the first chapter dealt with the general framework of the research, the second, third and fourth chapters dealt with the theoretical framework of research, the 5th chapter covered analyzing of study data , results explanation and the most important recommendations and suggestions , The most significant results showed that there is a moral effect relationship with statistical indication between the leading types and level of job satisfaction in each of the institutes. The democratic type is the most positively effective type on the job satisfaction , in addition , there is moral effect for some of demographic variables on the general job satisfaction level.